HUBUNGAN TINGKAT PENGETAHUAN IBU DENGAN SIKAP STIMULASI TUMBUHKEMBANG PADA ANAK BALITA - Mutia Arin Agustin; Esitra Herfanda (Jurnal Medicare, 2026)
Toddlerhood is a golden period that requires optimal growth and development stimulation. However, child development disorders in Indonesia still reach around 18% and SDIDTK coverage is only 70.8%, so maternal knowledge is an important factor in shaping attitudes towards stimulating children's growth and development. The purpose of this study was to analyze the relationship between maternal knowledge levels and attitudes towards stimulating growth and development in toddlers at ABA Jetis IV Kindergarten. The method used in this study was an analytical quantitative design using a cross-sectional approach. The sample consisted of 47 mothers with children aged 1-5 years, selected using simple random sampling. Data were collected using a validated knowledge and attitude questionnaire and analyzed using the Spearman Rank test (α < 0.05). The results showed that 87.2% of mothers had a good level of knowledge, with 61.7% showing a good attitude toward stimulation. The Spearman Rank correlation test indicated a significant relationship between the mothers' level of knowledge and their attitude towards stimulation of growth and development of 0.007 (p<0.05) with a correlation coefficient (0.385), which means that there is a relationship between the mothers' level of knowledge and their attitude towards stimulating the growth and development of toddlers at ABA Jetis IV Kindergarten with a low degree of relationship. The suggestion for future researchers is to expand the sample size and add other variables that may potentially influence children's growth and development stimulation attitudes.